1982
DOI: 10.1128/jb.150.1.414-417.1982
|View full text |Cite
|
Sign up to set email alerts
|

DNA isolated from Mycobacterium leprae: genome size, base ratio, and homology with other related bacteria as determined by optical DNA-DNA reassociation

Abstract: DNA derived from Mycobacterium leprae (grown in armadillos) was isolated, purified, and analyzed spectrophotometrically. The genome size and the guanineplus-cytosine content of M. leprae were 1.3 x 109 and 55.8%, respectively. Among selected strains of mycobacterial, nocardial, and corynebacterial species, Corynebacterium sp. 2628 LB, isolated from a human leprosy patient, showed the highest DNA homology with M. leprae. Of the DNAs derived from mycobacteria, those of M. tuberculosis and M. scrofulaceum showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…M. vaccae DNA has a G+C content similar to the reported values for other mycobacterial DNAs, which fall into two groups: one with G+C contents of 64 to 66.4% and the other with G+C contents of 67 to 70% (39). In contrast, M. leprae DNA has a G+C content significantly different from those of other mycobacteria, as has been reported by Imaeda et al (19). "M. lufu" DNA also has a G+C content that is lower than those of other mycobacterial DNAs.…”
Section: Resultssupporting
confidence: 53%
“…M. vaccae DNA has a G+C content similar to the reported values for other mycobacterial DNAs, which fall into two groups: one with G+C contents of 64 to 66.4% and the other with G+C contents of 67 to 70% (39). In contrast, M. leprae DNA has a G+C content significantly different from those of other mycobacteria, as has been reported by Imaeda et al (19). "M. lufu" DNA also has a G+C content that is lower than those of other mycobacterial DNAs.…”
Section: Resultssupporting
confidence: 53%
“…Current genetic information suggests that M. leprae is only minimally related to other mycobacteria according to guanine plus cytosine content (Clark-Curtiss etal.. 1985), genome size Imaeda et al, 1982), and DNA homoiogy as judged by fluid-phase reassociation kinetics (Imaeda etal., 1982) or solid-phase hybridization kinetics (Grosskinsky ef al., 1989). A comparison between M. leprae isolates by total genomic hybridization studies showed high levels of homoiogy, suggesting a high degree of relatedness between isolates (Imaeda etal.. 1982).…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility cannot be excluded that a portion of the antibodies is directed to cross-reactive determinants and results from a response to other mycobacteria. The established DNA sequences had a G+C content that was much higher than that reported for the M. leprae genome and more comparable to those of a number of other mycobacteria (10,17). Although the sequenced parts of the genes may not be representative for the complete genes, this might indicate that the expressed M. leprae determinants are not specific for this bacillus but could be common in a number of other pathogenic and nonpathogenic mycobacteria.…”
Section: Vol 58 1990mentioning
confidence: 76%